2003
DOI: 10.1562/0031-8655(2003)077<0349:boasog>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Base Oxidation at 5′ Site of GG Sequence in Double-stranded DNA Induced by UVA in the Presence of Xanthone Analogues: Relationship Between the DNA-damaging Abilities of Photosensitizers and Their HOMO Energies¶

Abstract: UVA contributes to skin cancer by solar UV light. Photosensitizers are believed to play an important role in UVA carcinogenesis. We investigated the mechanism of DNA damage induced by photoexcited xanthone (XAN) analogues (XAN, thioxanthone [TXAN] and acridone [ACR]), exogenous photosensitizers, and the relationship between the DNA-damaging abilities and their highest occupied molecular orbital (HOMO) energies. DNA damage by these photosensitizers was examined using 32P-labeled DNA fragments obtained from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 50 publications
2
28
0
Order By: Relevance
“…As INH possesses higher E T1 relative to TX, the direct energy transfer based deactivation pathway is unfeasible. Moreover, it is worth mentioning that as E T1 of TX is higher than the energy needed to bring 3 O 2 to singlet excited state ( 1 O 2 ), 1.05 eV false(3gΔg1) or 1.65 eV (3g1g+false), through direct energy transfer T 1 state TX can photogenerate singlet oxygen ( 1 O 2 ), which may be involved in the DNA photooxidation by TX [4]: TXfalse(T1false)+3O2TX+1O2…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As INH possesses higher E T1 relative to TX, the direct energy transfer based deactivation pathway is unfeasible. Moreover, it is worth mentioning that as E T1 of TX is higher than the energy needed to bring 3 O 2 to singlet excited state ( 1 O 2 ), 1.05 eV false(3gΔg1) or 1.65 eV (3g1g+false), through direct energy transfer T 1 state TX can photogenerate singlet oxygen ( 1 O 2 ), which may be involved in the DNA photooxidation by TX [4]: TXfalse(T1false)+3O2TX+1O2…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the electron transfer from T 1 state TX to INH (Equation 4) is theoretically unfeasible because of the positive value of total reaction energy (summation of AIP T1 of TX and AEA of INH). In previous study, the electron transfer-based DNA oxidation by photoexcited TX has been reported [4]. The electron transfer process has also been reported to be involved in the deactivation of T 1 state TX by amines or indolic derivatives [7,8].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their studies suggested that photo-excited TX induce nucleotide oxidation at 5 -G of GG sequence in doublestranded DNA via electron transfer. Potential mechanisms of action may include DNA intercalation, inhibition of nucleic acid biosynthesis as well as formation of intracellular DNA single strand breaks [11]. So far, the exact mechanism of anti-tumor action of TXs is unclear yet.…”
Section: Introductionmentioning
confidence: 99%
“…Photosensitizers, xanthone and its derivatives have been extensively examined for the UVA-induced DNA damage [9, 10]. It has been also known that xanthone mediates the photosensitized decomposition of fatty ester hydroperoxides to produce oxyl radicals [11] and hydroxyl radicals [12].…”
Section: Introductionmentioning
confidence: 99%